Comparative Analysis Of Saw And Topsis In Selecting Recipients Of Basic Food Assistance - Adhika Pramita Widyassari; Mohamad Ardy An’syah; Retno Wahyusari (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The Basic Food Program is one of the Indonesian government's alternative programs for distributing aid to underprivileged or poor communities. A selection process needs to be carried out to determine recipients of basic food assistance. Decision Support Systems are effective systems used to produce calculations with output in the form of rankings. The methods that are quite widely used are the Simple Additive Weighting (SAW) method and the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS). This research aims to apply the SAW and TOPSIS methods in selecting aid recipients so that appropriate results are obtained which can be proposed as solutions to decision-making problems. There are 6 criteria used in this case, including: residence, occupation of the head of the family, type of floor, type of wall, place to urinate, lighting source. The data used as a test is data from the Banyuurip village community in 2023. The calculation process is carried out by finding the weight value of each alternative for each criterion. The selected aid recipients are those who have the greatest value as the best alternative. From the calculation results of the SAW (Simple Additive Weighting) and TOPSIS methods, the calculation results of the two methods were obtained. The alternative with the largest value or rank 1 produced by SAW and TOPSIS was both selected as alternative A10. Of the 12 data tested, SAW and TOPSIS have 50% similar alternative ranking results, including: rank 1 = A10, rank 5 = A9, rank 7 = A7, rank 8 = A6, rank 11 = A2, and rank 12 = A12. The SAW method gets better results compared to the TOPSIS method, because it gets precise, stable results and shorter processing time.